The role of a pharmacist in the process of effective and safe intravenous fluid therapy - Adrian Bryla; Małgorzata Zygmunt; Krystyna Chmal-Jagiełło; Paweł Węgrzyn; Michał Steczko; Tomasz Buczek (Polish Pharmaceutical Society, 2021)
Fluid treatment is one of the basic medical procedures used in every hospital. To be properly conducted, it requires making complex decisions regarding the optimal volume, infusion rate, and type of fluids. Fluid therapy should only be used in patients with an insufficient oral or enteral route of fluid administration, and for the shortest possible time. Planning fluid therapy, the total and enteral fluid intake should be taken into account. There are many fluids that can be used and their choice should be reflected in the patient's condition. There are two types of substances whose solutions are used in parenteral fluid therapy: crystalloids and colloids. Crystalloids are the fluids of the first choice for intravenous fluid therapy: crystalloids remain for a relatively short time in the vascular tract, causing the extravascular water space to expand rapidly. Colloids are suspensions of macromolecules in solvents, whose task is to stabilize the intravascular water space. Pharmacovigilance is one of the most important elements of inpatient care. It is the pharmacist's task (as a specialist in the field of medicine and pharmacotherapy) to monitor the safety of the therapy. Scientific research shows that the participation of pharmacists in this process is necessary because they provide additional information that is not included in reports prepared by representatives of other medical professions. The task of the clinical pharmacist in the hospital ward is to analyze the ordered fluid therapy, a possible proposal for its correction, and above all, to analyze the prescribed solutions in terms of interactions with other medications used by the patient. Effective and safe pharmacotherapy depends on the rational selection of the appropriate medicinal product (taking into account not only active substances, but also auxiliary substances or buffers, which also affect the final therapeutic effect), proper selection of the optimal dosing schedule, and aseptic administration of the medicinal product. All this is aimed at eliminating the greatest possible number of side effects that may occur in the course of the patient's therapy